Heat and mass transfer analysis in air gap membrane distillation process for desalination - Pangarkar, Bhausaheb L.; Sane, Mukund G. (Membrane Water Treatment, 2011)
The air gap membrane distillation (AGMD) process was applied for water desalination. The main objective of the present work was to study the heat and mass transfer mechanism of the process. The experiments were performed on a flat sheet module using aqueous NaCl solutions as a feed. The membrane employed was hydrophobic PTFE of pore size 0.22 mu m. A mathematical model is proposed to evaluate the membrane mass transfer coefficient, thermal boundary layers' heat transfer coefficients, membrane/liquid interface temperatures and the temperature polarization coefficients. The mass transfer model was validated by the experimentally and fitted well with the combined Knudsen and molecular diffusion mechanism. The mass transfer coefficient increased with an increase in feed bulk temperature. The experimental parameters such as, feed temperature, 313 to 333 K, feed velocity, 0.8 to 1.8 m/s (turbulent flow region) were analyzed. The permeation fluxes increased with feed temperature and velocity. The effect of feed bulk temperature on the boundary layers' heat transfer coefficients was shown and fairly discussed. The temperature polarization coefficient increased with feed velocity and decreased with temperature. The values obtained were 0.56 to 0.82, indicating the effective heat transfer of the system. The fouling was observed during the 90 h experimental run in the application of natural ground water and seawater. The time dependent fouling resistance can be added in the total transport resistance.
Keywords: AGMD; Desalination; heat transfer coefficient; mass transfer coefficient; temperature polarization coefficient

Hydrodynamics, residence time distribution, and mass transfer in spiral coils in series - Khan, Muzammilanwar S.; Deore, Hital S.; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2023)
Here, we report the analysis of flow field, residence time distribution (RTD), and mass transfer for the novel design of a spiral coil reactor (SCR) consisting of five spiral coils connected in series. Each coil comprises 8 turns with minimum and maximum radii of curvatures of 15 and 45 mm, respectively. The SCR is made up of an SS 316 tube (1/8 in. approximate to 3.175 mm O.D. and 1.8 mm I.D.), with a total length of 3.89 m. Experiments, as well as three-dimensional (3D) CFD simulations, are carried out to study the effects of the flow rate (61 <= Re-in <= 1839) on spatial variations in velocity and pressure distribution within the individual coils of the reactor. The flow regime is observed to undergo a transition from stable laminar flow for a lesser Dean number (De < 50) to dominant secondary flow vortices for De > 80. During the flow from the inner to the outer turns of the coil, the tangential velocity increases with a decreasing curvature ratio (delta), and the opposite occurs during the flow from the outer to the inner turns of the coil. Experimental RTD results show that the extent of axial dispersion decays exponentially with increasing Re and remains constant for Re > 500. For liquid-liquid two-phase flow, the spiral coils in series offer a mass transfer coefficient comparable to those of static mixers and agitated contactors but with significantly lesser power consumption per unit volume. This work gives new insights into the design of a spiral coil reactor suitable to carry out single-phase and multiphase reactions efficiently as possibly the most space-filling option of tubular reactors with excellent transport characteristics.
Keywords: Gas- Liquid; heat transfer coefficient; Liquid Taylor Flow